Training of muscular endurance according to ongoing topical way by bio-mechanic indicators in the development of some of the capabilities of endurance and achievement to run 800 m - Hussein, Alia; jawad, zaydoon; Razak, baydaa (Journal of Physical Education, 2010)
In the door the first definition of research includes the introduction and importance of research in the development of stress-place of the muscles of the men on duty the actual ran 800 meters and its impact on the rate of speed and the number of steps and frequency in each session and put the problem of the transmission of athletes to the capacity of the physical through innovation in the training of strength and endurance necessary to improve achievement was the objective of this research the effect of using endurance-place of the muscles of the legs and the training of the length of step and frequency in the completion of 800 m in section III the researchers used the experimental method and included the sample (12) players in this section has procedures for search field and ways to obtain the information either in Part IV have been Showing results through two tables and display written and discussed in section V has been the most important conclusions :ØEvolution of the average speed and frequency and length of steps in the experimental group.ØThe control group did not achieve significant developments in the achievement and the variables by bio-mechanic.